Between Entertainment and Elegy: The Unexpected Success of R. C. Sherriff's Journey's End (1928). (11th March 2016) - Walters, Emily Curtis
Abstract: Despite West End producers' and critics' expectations that it would never turn a profit, R. C. Sherriff's Journey's End (1928) became the most commercially successful First World stage drama of the interwar period, celebrated as an authentic depiction of the Great War in Britain and around the world. This article explains why. Departing from existing scholarship, which centers on Sherriff's autobiographical influences on his play, I focus instead on the marketing and reception of this production. Several processes specific to the interwar era blurred the play's ontology as a commercial entertainment and catapulted it to international success. These include its conspicuous engagement with and endorsement by veterans of the war, which transformed the play into historical reenactment; the multisensory spectatorial encounter, which allowed audiences to approach Journey's End as a means of accessing vicarious knowledge about the war; and a marketing campaign that addressed anxieties about the British theatrical industry. Finally, I trace the reception of this play into the Second World War, when British soldiers and prisoners of war spontaneously revived it around the world. The afterlives of Journey's End, I demonstrate, suggest new ways of conceiving of the cultural legacy of the First World War across the generations.